An omega-3 polyunsaturated fatty acid concentrate administered for one year decreased triglycerides in simvastatin treated patients with coronary heart disease and persisting hypertriglyceridaemia. Issue 5 (1st May 2001) - Durrington, P N; Bhatnagar, D; Mackness, M I; Morgan, J; Julier, K; Khan, M A; France, M
Abstract : BACKGROUND: Omega-3 fatty acids, such as those present in fish oil, have been reported to prolong life in myocardial infarction survivors. These fatty acids can decrease serum triglyceride concentrations, but so far the doses used in trials examining their effects on coronary end points have had only minimal triglyceride lowering effects. OBJECTIVE: To examine the triglyceride lowering effectiveness, safety, and tolerability of Omacor, a concentrate of omega-3, long chain, polyunsaturated fatty acids from fish oil (84% of the total as opposed to an average of 35% in fish oil) over one year in patients with established coronary heart disease (CHD) and persisting hypertriglyceridaemia, despite receiving simvastatin in doses similar to those employed in the Scandinavian simvastatin survival study. SUBJECTS AND METHODS: 59 patients with CHD, receiving simvastatin 10–40 mg daily with serum triglycerides > 2.3 mmol/l, were randomised to receive Omacor 2 g twice a day or placebo for 24 weeks in a double blind trial. Forty six patients accepted the offer of active treatment for a further 24 weeks in an open phase of the trial. RESULTS: There was a sustained significant decrease in serum triglycerides by 20–30% (p < 0.005) and in very low density lipoprotein (VLDL) cholesterol by 30–40% (p < 0.005) in patients receiving active Omacor at three, six, and 12 months compared either to baseline or placebo. Omacor did not have any deleterious effect on low density or high density lipoprotein cholesterol or on biochemical and haematological safety tests. There was no adverse effect on glycaemic control in patients with diabetes, who showed a decrease in serum triglyceride, which was at least as great as in non-diabetic patients. One patient receiving placebo died of acute myocardial infarction. Three patients withdrew from the trial (two on placebo and one on active treatment). Omacor was generally well tolerated. CONCLUSION: Omacor was found to be a safe and effective means of lowering serum triglycerides over one year in patients with CHD and combined hyperlipidaemia, whose triglycerides remained elevated despite simvastatin treatment.